Determination of Leading Fruit Commodities in Barat Miomaffo District (Sallu Village Case Study) - Soi, Maria Nelde; Taena, Werenfridus; Joka, Umbu (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen AgribisnisDO - 10.24843/JMA.2023.v11.i01.p12, 2023)
Determination of Leading Fruit Commodities in West Miomaffo District (Case Study of Sallu Village). This study aims to 1) determine the superior commodity of fruits based on the Location Quotient approach. 2) determine the fruit commodity based on the Analytical Hierarchy Process approach. The research was conducted using Location Quotient analysis and Analytical Hierarchy Process. The results showed that based on 1) the results of the LQ analysis stated Avocado, Mango, Jackfruit as superior commodities. 2) AHP results show that avocado with the largest weight value is 0.310. while the value of other commodities sequentially is oranges with a weight value of 0.265. mango with a weight value of 0.141 mango. and jackfruit with a weight value of 0.116. Based on the LQ and AHP values, quadrant analysis was carried out with the results of quadrant I it was known that avocado fruit was the leading commodity according to the results of the LQ (>1) and AHP (>0.25) analysis, quadrant II it was known that mango and jackfruit were superior commodities based on the analysis LQ (>1). While the results of AHP (<0.25) quadrant III revealed that citrus fruit is a leading commodity based on AHP (>0.25) while the results of LQ analysis (<1) stated that citrus is not a leading commodity.